Analisis sitiran dan pemetaan deskriptor terhadap disertasi Program Pascasarjana Universitas Islam Negeri Imam Bonjol - Muntashir Muntashir; Erida Erida (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2018)
This study aims create a bibliometrics profile of the dissertation of postgraduate program Imam Bonjol State Islamic University. The dissertation consists of two doctoral programs namely Islamic education and Islamic law. Bibliometrics studies related to characteristics citation analysis, half life calculation and bibliometrics mapping of dissertation. This research uses bibliometrics method with quantitative approach. As for the unit of analysis is the whole dissertation of 67. Analysis of citation analyzed frequency and percentage calculation and mapping is built using VosViewer software.The resultant, The citation pattern of the most cited author in the dissertation of Islamic education with the four highest levels is Abuddin Nata, Ramayulis, Ministry of Religious Affairs and Azyumardi Azra. Next to Islamic law are Yusuf al-Qaradawi, Amir Syarifuddin, Mustafa al-Zuhaili and Muhammad Abu Zahrah. The most cited literature type in book form in the dissertation of Islamic Education reaches 88.15% and Islamic law 94.97%. Based on the pattern of the literature language cited for the dissertation of Islamic education is still dominated by the Indonesian language with 83%, then there is a significant difference with the citation of the Islamic law dissertation where Indonesian language reaches 45% and Arabic language reaches 52%. Related to the obsolescence of literature based on the living part of the age of getting for the dissertation of Islamic education is 24 years and 32 years of Islamic law. Based on the map descriptor can be explained trends of research topics from dissertation of Islamic education, more research topics on curriculum development research, madrasah management model including college. Clusters of topics related to the thoughts of Muslim scholars and Islamic educational leaders. The next cluster is the implementation of management in the madrasah. The research topic trends contained in the dissertation of Islamic law programs, namely renewal, jurisprudence, and customary law related to marriage include inheritance.